Suppression of the Lycopene Cyclase Gene Causes Downregulation of Ascorbate Peroxidase Activity and Decreased Glutathione Pool Size, Leading to H2O2 Accumulation in Euglena gracilis - Tamaki, Shun; Sato, Ryosuke; Koshitsuka, Yuki; Asahina, Masashi; Kodama, Yutaka; Ishikawa, Takahiro; Shinomura, Tomoko (Frontiers in Plant Science, 2021)
Carotenoids are photosynthetic pigments and hydrophobic antioxidants that are necessary for the survival of photosynthetic organisms, including the microalga Euglena gracilis. In the present study, we identified an uncharacterized gene encoding the E. gracilis β-carotene synthetic enzyme lycopene cyclase (EgLCY), and discovered a relationship between EgLCY-mediated carotenoid synthesis and the reactive oxygen species (ROS) scavenging system ascorbate-glutathione cycle. The EgLCY cDNA sequence was obtained via homology searching E. gracilis transcriptome data. An enzyme assay using Escherichia coli demonstrated that EgLCY converts lycopene to β-carotene. E. gracilis treated with EgLCY double-stranded RNA (dsRNA) produced colorless cells with hypertrophic appearance, inhibited growth, and marked decrease in carotenoid and chlorophyll content, suggesting that EgLCY is essential for the synthesis of β-carotene and downstream carotenoids. In EgLCY dsRNA-treated cells, the ascorbate-glutathione cycle, composed of ascorbate peroxidase (APX), dehydroascorbate reductase (DHAR), monodehydroascorbate reductase (MDAR), and glutathione reductase (GR), was unusually modulated; APX and GR activities significantly decreased, whereas DHAR and MDAR activities increased. Ascorbate content was significantly increased and glutathione content significantly decreased in EgLCY dsRNA-treated cells and were correlated with their recycling enzyme activities. Fluorescent imaging demonstrated that EgLCY dsRNA-treated cells accumulated higher levels of H2O2 compared to wild-type cells. Taken together, this study revealed that EgLCY-mediated synthesis of β-carotene and downstream carotenoid species upregulates APX activity and increases glutathione pool size for H2O2 scavenging. Our study suggests a possible relationship between carotenoid synthesis and the ascorbate-glutathione cycle for ROS scavenging in E. gracilis.